1984
DOI: 10.1016/0741-5214(84)90011-9
|View full text |Cite
|
Sign up to set email alerts
|

Early carotid endarterectomy in patients with small, fixed neurologic deficits

Abstract: Patients who have sustained a large hemispheric stroke are not candidates for early carotid endarterectomy, but there is less agreement regarding the role of carotid endarterectomy in patients with small, fixed neurologic deficits. Accepted practice in many centers is to wait 4 to 6 weeks after the onset of the deficit before proceeding with carotid endarterectomy because of the fear that early revascularization will increase the size of the infarct. Earlier endarterectomy, however, in patients with significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
6

Year Published

1988
1988
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 8 publications
2
12
0
6
Order By: Relevance
“…Patients with a stable acute stroke and normal CT scan can undergo CEA with no increased risk shortly after diagnosis. 11,14,15,17,22 Advancements in thrombolytic therapy currently provide patients a significant opportunity for neurological recovery after an acute ischemic event. tPA has been shown to be safe and effective in the treatment of acute stroke when administered within 3 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a stable acute stroke and normal CT scan can undergo CEA with no increased risk shortly after diagnosis. 11,14,15,17,22 Advancements in thrombolytic therapy currently provide patients a significant opportunity for neurological recovery after an acute ischemic event. tPA has been shown to be safe and effective in the treatment of acute stroke when administered within 3 hours.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Therefore, it is prudent to exclude patients with mental status changes or severe hemiparesis from surgical intervention. 11,14,16,19 That severity of neurologic deficit as classified by the modified Rankin score did not significantly influence outcome in our series (Table 6), does not refute this experience but underscores the importance of patient selection, excluding from immediate surgery patients with severely debilitating deficits.…”
Section: Discussionmentioning
confidence: 73%
“…2 Several authors have since reported favorable results with a more aggressive approach to selected patients with recent neurologic deficit reporting combined stroke/mortality rates between 0.9 and 7.4%. 10,11,[14][15][16][17][18][19] Although selection criteria have varied individually, several general principles are beginning to emerge.…”
Section: Discussionmentioning
confidence: 99%
“…In weiteren Auswertungen der ECST-und NASCET-Daten konnten klinische und morphologische Subgruppen mit einer [16,23,40,58].…”
Section: Klinische Subgruppenunclassified